BOOK REVIEW FATWA IN INDONESIA: AN ANALYSIS OF DOMINANT LEGAL IDEAS AND MORE OF THOUGHT OF FATWA-MAKING AGENCIES AND THEIR IMPLICATIONS IN THE POST-NEW ORDER PERIOD - Susetyo, Heru (UI Scholars Hub, 2020)
The book was written by Dr. Pradana Boy ZTF, a lecturer at Faculty of Islamic Studies Universitas Muhammadiyah Malang, and a prominent scholar of Muhammadiyah is derived from his dissertation at the National University of Singapore (NUS) in 2015. This book looks at fatwa in Indonesia during the fall of President Suharto (New Order) in 1998. It is about the exploration of three fatwa-making agencies namely Majelis Ulama Indonesia (Indonesian Council of Ulama), Lajnah Bahtsul Masail Nahdlatul Ulama (‘Bahtsul Masail’ means discussion of the problems), and Majelis Tarjih Muhammadiyah (‘Majelis Tarjih’ means ‘Assessment Council’).